Towards a Re-Conceptualization of the Pathway of Agricultural Technology for a Better Impact Assessment - Moumouni, Ismail; Baco, Mohamed N.; Idrissou, Latifou (International Journal of Publication and Social Studies, 2019)
There is incredibly a large consensus on research methodology and agreement on research results in agricultural technology adoption studies conducted in the past decades. This paper provides an explanation to such a consensus by questioning its foundation and wonder whether there are some conceptual alternatives. A paradigmatic analysis of adoption studies shows that innovation is generally considered as a definitively shaped idea/object to be either adopted or rejected. Such a representation of the pathway of agricultural technology led to the standardization of research designs and the underestimation of the impact of technology. Technology adoption models shifted to methodological sophistication that resulted in the oversimplification of reality. The paper suggests a re-conceptualization of the methodology for a better impact assessment of technology. Interpretive methods could be used as a complement to positivist methods that reduce the complexity of innovation pathways assessment. This would provide a comprehensive view of the adoption process and may help researchers to formulate future research in the area.